INFLUENCE OF THE FILLER TYPE ON STRENGTH AND THERMAL PROPERTIES OF EXOTHERMIC BLENDS - D. M. Kukuj; Ju. N. Fasevich; A. I. Turok (Литьë и металлургия)
The influence of filler on strength and thermal properties of exometric blends is shown. It is determined that input quantities of lightweight filler exert considerable influence on strength properties of exometric blend.